RELATIONSHIP OF MOTHER KNOWLEDGE ABOUT EXCLUSIVE BREAST FEEDING WITH SUCKLING WAY IN THE PUSKESMAS REGION WORK OF KARANGDOWO KLATEN - Ika Eny Nursanti; Kemaludin .; Heny Kurniawati (STIKES DUTAGAMA KLATEN, 2013)
When baby born actualy require nutritious food, so to be can become achievement generation and good for state and nation. To realize that thing is one of the its way by giving exclusive breast feeding early on. Efficacy in suckling also influencing by knowledge losing of knowledge about suckling to mean losing of big knowledge, because suckling is an knowledge having important role in maintaining human life. Important therefore him suckle also will influence giving of exclusive breast feeding at baby hence conducted by research about Relationship Of Mother Knowledge About Exclusive Breast Feeding With Suckling Way In The Puskesmas Region Work Of Karangdowo Klaten.